2014
DOI: 10.1002/fuce.201300111
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Study of Yttria‐Based Glasses with High‐Temperature Electrolyte for SOFC

Abstract: The chemical interaction study of AO–SiO2–B2O3–Y2O3 (A = Ba, Sr) (BaY, SrY) glass with high‐temperature electrolyte yttria‐stabilized zirconia (YSZ 8 mol%) is reported as a function of different heat treatment durations. The as‐prepared glass with 10 mol% of yttria shows limited amount of crystallization at 800 °C. Due to this yttria‐based glasses BaY and SrY have been chosen to make diffusion couples with high‐temperature electrolyte and interconnect material. These diffusion couples have been heat treated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…La 2 O 3 ‐ and Y 2 O 3 ‐containing glasses have been reported by many researchers 67,72,93,94,188,216–226 . La 2 O 3 acts as a modifier or former, depending on the initial composition of the glass.…”
Section: Effect Of Different Glass Constituents On Sealing Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…La 2 O 3 ‐ and Y 2 O 3 ‐containing glasses have been reported by many researchers 67,72,93,94,188,216–226 . La 2 O 3 acts as a modifier or former, depending on the initial composition of the glass.…”
Section: Effect Of Different Glass Constituents On Sealing Propertiesmentioning
confidence: 96%
“…These glasses showed good bonding with YSZ and Crofer 22APU. Laorodphan et al 212 67,72,93,94,188,[216][217][218][219][220][221][222][223][224][225][226] La 2 O 3 acts as a modifier or former, depending on the initial composition of the glass. Kaur et al 67 reported that the crystallization process is faster in the SrO-SiO 2 -B 2 O 3 -La 2 O 3 (SL) glass sealant than in BaO-SiO 2 -B 2 O 3 -La 2 O 3 (BL) glasses.…”
mentioning
confidence: 99%